RUNNING DICTATION TO IMPROVE EFL STUDENTS’ WRITING - Fitri Nurdianingsih; Oktha Ika Rahmawati (LPPM Press STKIP PGRI Pacitan, 2018)
This article refers to a classroom action research by implementing running dictation in teaching writing. Running dictation is fairly easy to prepare, explain, set up, and adaptable. Dictation activities also promote the conscious learning of structures. The subject of the study was the fourth semester of English department students in one private university in Bojonegoro. Running dictation was implemented in three cycles. The result shows that the implementation of running dictation in teaching writing can help students in their writing.